ZOLTÁN BIEDERMANN, ANNE GERRITSEN, GIORGIO RIELLO (eds.), Global Gifts. The Material Culture of Diplomacy in Early Modern Eurasia, Cambridge 2018, Cambridge University Press, 301 pp., ISBN 978-1-108-41550-7 - Čapská, Veronika (Dějiny – teorie – kritika, 2018)
Book review